Overview of potential drugs for the treatment of new coronavirus Infection (COVID-19) - Ya. E. Shirobokov; E. P. Gladunova; E. A. Borodulina; A. E. Sukhanova (Acta Biomedica Scientifica)
The new coronavirus infection (SARS-CoV-2), better known as COVID-19, quickly evolved into a worldwide pandemic with a significant public health burden. Currently, there are no approved drugs or preventive therapeutic strategies to combat infection. Decisions about prescribing many medications are made based on the results obtained in in vitro studies, or expert opinions. Most of the drugs currently used to treat COVID-19 are approved antivirals or antibodies against other diseases. However, there are hundreds of clinical studies underway around the world to discover effective treatments for COVID-19. This article summarizes the results of clinical studies of potential therapeutic drugs used as COVID-19 therapy. Based on this review, it can be concluded that there is still no high-quality evidence to support any of the drugs described below. Until the unambiguous results of randomized controlled trials are available, the use of any of the following drugs is not clinically proven as an effective treatment for COVID-19.